Identificación y evaluación de riesgos biológicos y su incidencia en la inocuidad de los procesos de elaboración en el laboratorio de cárnicos de la unidad académica CAREN de la Universidad Técnica de Cotopaxi durante el periodo 2016 - Ruiz Guato, Mónica Carina (2016)
This research project was developed in the laboratory of meat at the Academic Unit of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, Salache campus. The study was conducted in order to set a precedent in the safety of products made experimentally in the laboratory, because of the importance of quality and food safety that being submitted processed products; it was necessary the identification and the analysis of biological risks in the production process of sausages and meat products in the laboratory by a risk matrix that was the basis for the design, development and implementation of a Manual of Good Manufacture Practices. Once the project was finished, the researcher set the parameters which regulate GMP regulation to obtain a certification under the 3253 agreement of the Rules of Good Practice for Processed Foods.